PROSES PENGERINGAN GABAH PADA INDUSTRI PEMBENIHAN PADI DI PT. PADI NUSANTARA MANGIR – ROGOJAMPI: Grain Drying Process at Rice Seed Industry PT. Padi Nusantara Mangir - Rogojampi - Aldelina Gina Damayanti, Rosiana Ulfa, Bagus Setyawan (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2022)
The agricultural commodity that is generally grown by the Indonesian population is rice. Rice will produce grand which is then processed inti rice. The provision of quality rice seeds in terms of high productivity is a factor to determine the increase in rice production in agriculture development. An effort made by the government to increase rice production was also followed by an increase in post-harvest activities utilizing intensification and extensification. The purpose of this fieldwork practice is to find out the flow of rice seed production and the process of drying grain at PT. Padi Nusantara. Methods of data collection were carried out in three ways, namely interviews, observations, and literature studies. Observations showed that the main key in determining the quality of the seeds produced was at the drying stage of rice seeds, which was able to reduce the moisture content of dry grain harvested by 13%.